“And when I think, alas! in tears of what was then and what is now”. An Anthropological-Historical Analysis of the Young and the Old Age in the Poetry of François Villon - Kulesza, Kamila (Starość i młodość w literaturze i kulturze, 2016)
The main aim of this paper is to analyse the medieval image of young and old age as presented insome poems of François Villon. The analysis, based on the heremeneutic reading of Villon’s poems andinspired by works of the scholars of Annales tradition, focuses on the question of social worth of individualsas determined by their age, with the special reference to the fate of medieval women, condemnedby culture to inevitable loneliness.